National Service for Health : the Labour Party's post-war policy (London : Labour Party)
1943-04 1943 1940s 24 pages NATIONAL SERVICE FOR HEALTH Do we need a State Medical Service? If so, on what lines should it be planned? This pamphlet summarises the Labour Party's answers to these two questions, which concern everyone in the land. PART I IS A STATE MEDICAL SERVICE NEEDED? Before answering the first question, we must decide what we require of the Health and Medical Services in general. (See Chapter I.) We must know, broadly, what the existing Medical Service is like. (See Chapter II.) We can then judge whether the Service, on its present basis, is likely to meet the need, or whether a State Medical Service is essential. (See Chapter III.) CHAPTER I WHAT MEDICAL SERVICES DO WE NEED? Britain's Health Aim The aim of the nation's Health policy can be nothing less than the utmost possible fitness of body and mind for all the people. Full health. We cannot afford to aim at anything less than that; for full health is the greatest asset of an individual, and a healthy population is the greatest asset of a nation. Health and Government To achieve this aim we need as good a Medical Service as possible. We need much more than that, however. We need social action to create the conditions under which the healthy needs of the whole people can be satisfied. In truth, there is hardly any activity of government which does not affect health, directly or indirectly. If, through a sound social and economic policy, we can master poverty, we shall thereby do much to eliminate ill-health; for poverty is still the greatest single cause of ill-health. If, by good government, we secure for all good conditions of work, with full employment, and with ample opportunity for leisure and exercise; if, through our public services, the citizen can obtain well-built and well-placed houses, with sanitation, water, clean and plentiful milk and other nourishing food, clean air and as much sunlight as possible, and freedom from injurious noise; then the health of the nation will benefit far more from these causes than from much doctoring. If our economic and social conditions are such that no removable barriers stand in the way of happy parenthood and healthy childhood, then we may reasonably hope that the population, instead of diminishing sharply and progressively, will be kept replenished by a sufficiency of children, well-born and well-nurtured. 2 36/H24/40